1972
DOI: 10.1139/v72-024
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Studies on Rotational Isomerism. VI. Normal-Coordinate Analysis of 2-Chloro-, 2-Bromo-, and 2-Cyanoethanol

Abstract: A normal-coordinate analysis of three substituted ethanol molecules X-CH,-CH,-OH (where X = CI, Br, or CN) was carried out using the simple valence force field model, and a computer program of Schachtschneider translated into Fortran language by Brooks. The effect of internal hydrogen bonding was studied by adding one extra symmetry coordinate, H . . . X (two, H . . . C and H . . . N, in the case of 2-cyanoethanol).The corresponding force constants show a good correlation with the hydrogen bond strengths. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…2-Chloroethanol (2CE) is the simplest chlorohydrin (aka ethylene chlorohydrin) and is a commonly used solvent or reactant, that has been widely used as a precursor in the large scale synthesis of oxirane (aka ethylene oxide) . It has found use as a relatively clean source for the pyrolytic production of the known interstellar molecule vinyl alcohol, , and its three low energy rotamers makes it a useful species for investigating interconversion enthalpies, both in the gas phase, , and in liquid rare gases. , In those studies, infrared spectroscopy was used for characterization of the different conformers of 2CE, which have good frequency separation between them, naturally depending on the vibrational mode . While lower resolution vibrational spectroscopy has resulted in the detailed characterization of the various band origins, the only high resolution study on 2CE that has been reported is in the microwave region .…”
Section: Introductionmentioning
confidence: 99%
“…2-Chloroethanol (2CE) is the simplest chlorohydrin (aka ethylene chlorohydrin) and is a commonly used solvent or reactant, that has been widely used as a precursor in the large scale synthesis of oxirane (aka ethylene oxide) . It has found use as a relatively clean source for the pyrolytic production of the known interstellar molecule vinyl alcohol, , and its three low energy rotamers makes it a useful species for investigating interconversion enthalpies, both in the gas phase, , and in liquid rare gases. , In those studies, infrared spectroscopy was used for characterization of the different conformers of 2CE, which have good frequency separation between them, naturally depending on the vibrational mode . While lower resolution vibrational spectroscopy has resulted in the detailed characterization of the various band origins, the only high resolution study on 2CE that has been reported is in the microwave region .…”
Section: Introductionmentioning
confidence: 99%